2018
DOI: 10.5152/tjg.2018.17467
|View full text |Cite
|
Sign up to set email alerts
|

Shorter waiting times from education to colonoscopy can improve the quality of bowel preparation: A randomized controlled trial

Abstract: (polyps, 42.2% vs. 38.5%, P=.667; adenoma, 31.2% vs. 22.7%, P=.275

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“… 4 , 19 Patients’ personal characteristics, including age, sex, body mass index, educational level, annual income, complications, and waiting time, can affect the quality of bowel preparation. 7 , 8 , 20 , 21 Thus, education becomes an important means to motivate patients and improve compliance for colonoscopy preparation. Studies have demonstrated the effectiveness of various patient educational methods to enhance bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 19 Patients’ personal characteristics, including age, sex, body mass index, educational level, annual income, complications, and waiting time, can affect the quality of bowel preparation. 7 , 8 , 20 , 21 Thus, education becomes an important means to motivate patients and improve compliance for colonoscopy preparation. Studies have demonstrated the effectiveness of various patient educational methods to enhance bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In the CG, however, as the waiting time extended, BBPS scores and adequate BP rates decreased gradually. Two studies support this result (36)(37) . It may not be feasible for each unit to reduce waiting times for colonoscopy due to patient load.…”
Section: Discussionmentioning
confidence: 71%
“…Sin embargo, las puntuaciones obtenidas por el GC en la BBPS y sus tasas de PI adecuada disminuían gradualmente de acuerdo con el tiempo de espera para la programación. Dos estudios corroboraron este resultado (36)(37) . Puede no ser posible para las unidades reducir el tiempo de espera para programar la colonoscopia, debido a la demanda de los pacientes.…”
Section: Discussionunclassified